Distribution and Abundance of Javan Primates in Gunung Sanggabuana, Karawang, West Java - Lindayu, Feriska; Utami, Marcelita Putri; Saidatinah, Salsa Mumtaz; Al Hanif, Syivaul Jannah; Priandani , Tasya Azzahra; Atmoko, Sri Suci Utami (Universitas Nasional Jakarta, 2024)
Indonesia, as the country with the highest number of primate species in Asia, also holds the largest number of endemic primates, including five species on the island of Java. This study aimed to assess the distribution and abundance of primate species in Gunung Sanggabuana, Karawang, West Java, one of the closest tropical rainforests to Jakarta. Field surveys were conducted during the dry season (11–14 September 2023) by the Primate Student Team of Field Biology Study (SBL). Recce transects were used for primate censuses and fruit trails for recording fruit-bearing plant abundances along two paths: the tourist area and semi-tourist area. Results indicated three primate species were directly encountered: Javan langur (Trachypithecus mauritius), Surili (Presbytis comata), and Javan gibbon (Hylobates moloch). In the Kejayaan-Burahol trail, Javan langurs were observed at 1 group/km (1–5 individuals), Surili at 0.5 groups/km (4 individuals), and Javan gibbons at 1 group/km (4–6 individuals). The Cigentis-Cipiit trail yielded higher Javan langur abundance at 1.5 groups/km (5–8 individuals). The dominance of Javan langur was noted with a low value of 0.160. These findings provide insight into primate distribution and abundance, contributing to conservation efforts in Gunung Sanggabuana and other Javan rainforests.